Synthesis of an Artificial Vitis Vinifera Mirna 319e Using Overlapping Long Primers and Its Application for Gene Silencing - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
The conserved mechanism of action of micro-RNAs (miRNAs) as regulators of gene expression has allowed the use of artificial miRNAs (amiRNAs) as a powerful tool for candidate gene evaluation in plants. Based on the use of a Vitis vinifera miRNA molecule (i.e., vvi-miR319e), the present work presents a new methodology for designing artificial miR319e precursors (pre-amiR319e). As a proof of concept, we silenced the green fluorescent protein (GFP) gene in transgenic Nicotiana benthamiana plants. This methodology includes a two-step PCR reaction in which overlapping long primers allow for the complete generation of pre-amiR319e-GFP molecules that are adequate for recombination into Gateway vectors with no further requirements. The seed region in amiRNA was directed against the 3 -end portion of the GFP gene. Three groups of transformed N. benthamiana plants were generated: GFP-, amiR319e-GFP-, and GFP plus miR319e-GFP-expressing vectors. A similar group of wild-type plants was included. Confocal microscopy evaluation of these groups revealed strong silencing of the GFP phenotype in the double GFP plus amiR319e-GFP group. The molecular characterization of silenced plants was achieved via modified 5 RACE of the GFP mRNA and revealed the occurrence of a partial, 3 -end GFP mRNA molecule that was generated in planta. In addition, large-scale small RNA sequencing confirmed the occurrence of the expected 21-nt miR319e-GFP species and other 22- and 24-nt species that exhibited sequence relationships with the expected amiRNA. These results highlight the possibility of using vvi-MIR319 as a template for the generation of single amiRNAs as a tool for gene silencing in plants. (C) 2016 Elsevier B.V. All rights reserved.